Determinan Pembiayaan Bermasalah di BTN Syariah KCS Bekasi Pada Masa Pandemi - Yulianti, Velia Dwi; Supriyanto, Trisiladi; Rahmi, Mira (Etihad: Journal of Islamic Banking and Finance, 2021)
The covid-19 pandemic has an impact on the community on their income, this affects people who have financing in banks where there are obstacles in paying their installments. This study aims to analyze and prove the effect of monitoring financing, business conditions, customer character, guarantees, and the covid-19 pandemic on non-performing financing at BTN Syariah KCS Bekasi. The population of this study is customers who have problematic financing at BTN Syariah KCS Bekasi. The sampling technique in this study is the Simple Random Sampling method. In this study, the source of the data obtained was the distribution of questionnaires by obtaining 127 respondents. The data analysis technique used is the SmartPLS 3.0 tool. The results obtained from this study are Financing Monitoring has a significant effect on non-performing financing, Business Conditions has no significant effect on non-performing financing, Customer Character has no significant effect on non-performing financing, Guarantee has no significant effect on non-performing financing, and the Covid-19 pandemic had a significant effect on non-performing financing.Pandemi covid-19 memberi dampak pendapatan kepada masyarakat. Hal ini yang memberi pengaruh pada kepemilikan pembiayaan di perbankan berupa kendala angsuran pembayaran. Penelitian ini bertujuan untuk menganalisis serta membuktikan pengaruh pemantauan pembiayaan, kondisi usaha, karakter nasabah, jaminan, dan pandemi covid-19 terhadap pembiayaan bermasalah di BTN Syariah KCS Bekasi. Populasi penelitian yaitu nasabah yang memiliki pembiayaan bermasalah di BTN Syariah KCS Bekasi. Teknik pengumpulan sampel dengan metode Simple Random Sampling. Adapun sumber data yang didapatkan dengan penyebaran kuesioner memperoleh 127 responden. Teknik analisis data yang digunakan dengan alat SmartPLS 3.0. Hasil penelitian menunjukkan bahwa pemantauan pembiayaan berpengaruh signifikan terhadap pembiayaan bermasalah, kondisi usaha tidak berpengaruh signifikan terhadap pembiayaan bermasalah, karakter nasabah tidak berpengaruh signifikan terhadap pembiayaan bermasalah, jaminan tidak berpengaruh signifikan terhadap pembiayaan bermasalah, dan pandemi Covid-19 berpengaruh signifikan terhadap pembiayaan bermasalah.